Awards: FOCS 2013 [2 awards] (2013 IEEE 54th Annual Symposium on Foundations of Computer Science, 2013)
The Machtey Award for Best Student Paper: The program committee of FOCS 2013 gives the Machtey Award to Jonah Sherman for his paper "Nearly Maximum Flows in Nearly Linear Time." This award is given annually at FOCS to the most outstanding paper written solely by one or more students. Best Paper Award: The program committee of FOCS 2013 gave Best Paper Awards to "Interlacing Families I: Bipartite Ramanujan Graphs of All Degrees" by Adam Marcus, Daniel A. Spielman and Nikhil Srivastava; "Navigating Central Path with Electrical Flows: from Flows to Matchings, and Back" by Aleksander Madry; and "On Kinetic Delaunay Triangulations: A Near Quadratic Bound for Unit Speed Motions" by Natan Rubin.